The Hybrid System of Prognosing in an Enterprise - Kiełtyka, Leszek; Jędrzejczyk, Waldemar (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The dissertation discusses the notion of the hybrid system. It presents the conception of the hybrid system of supporting the construction of economic prognoses in an enterprise. The authors demonstrate two approaches - traditional and innovative. What is more, the paper determines the mode of integrating methods in the given stage of the prognosing process. Finally, it presents the conditions of die implementation of the innovative approach to the proposed hybrid prognosing system.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 81-88